PRACTICALITY TEST OF â€œSTEPPING THE 5 STAIRS A TECHNIQUEâ€ ON GRAMMAR FOR COLLEGE STUDENTS: RASCH MODEL ANALYSIS - Agust, Satria (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Exposing research data by using unreliable applications bring about research findings to the brink of collapse. Unlike other applications, Rasch model application can analyze research data as it is. It can also dismiss researchersâ€™ hubbub and anxiety. This application is used to analyze research instrument on development of a teaching technique on grammar for college students. The objective of this research is to analyze practicality test instrument used in research and development on grammar technique, â€œStepping the 5 Stairs Aâ€ for college students by using Rasch model. This research was descriptive quantitative. The setting of this research was in a university in Riau Isle and was conducted in May 2018. The first-year students of English Education in 2017/2018 academic year became the research subject. This research results that the analysis of the practicality test instrument by using Rasch model shows the above average logit item (+0.00 logit) emphasizing participantsâ€™ approval on the quality of the instrument. Different perspectives which participants give through the instrument fulfilment describe their present conditions which are necessary to have further investigation in this research.